Perancangan Perawatan Mesin Cetak Offset Dengan Pendekatan RCM, (Reliability Centered Maintenance): (Studi Kasus Pada Cv Madyotomo Jawa Tengah) - Apif Sofyan; Indah Wahyu Utami; Ringgo Ismoyo Buwono (Jurnal Rekayasa Proses dan Industri Terapan, 2024)
Machines play a crucial role in a production process, highlighting the need for maintenance to ensure their proper functioning. The methods employed include Fault Tree Analysis (FTA), Failure Mode and Effect Analysis (FMEA), and distribution determination. The repair times for each CMYK component are as follows: the bearing component requires 93.541 hours or 4 days, Griver needs 163.235 hours or 7 days, the seal requires 195.349 hours or 9 days, the linner pen needs 248.803 hours or 10 days, and the ink tank needs 260.123 hours or 11 days.